Academic freedom in Africa : a case for the interpretation of the African Charter on Human and Peoples' Rights as providing protection for the human right to academic freedom - Vahard, Patrice (University of Pretoria, 2010)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.